Draft Second 5-Year Plan of Madhya Pradesh 1956-57—1960-61 Part I Appreciation and Programme for First Year - Planning Commission (Planning Commission, 1956)
This Plan was discussed with the Planning Commission in May,1951, and it was suggested that the five year cost should be reduced to Rs. 44.76 crores. Central assistance consisting of loans and grants was limited to Rs. 8 crores only; this was later increased to Rs. 12 crores. Based on these discussions, the State Plan was reviewed and the revised Plan was of Rs. 43.48 crores. The State Plan as finalised stood at Rs. 43.08 crores at the beginning of the First plan period.
Government of Madhya Pradesh